The Real Estate Market in the Context of Municipal Management. Example of the Lublin Functional Area - Dagmara Kociuba; Andrzej Matacz (Barometr Regionalny, 2018)
The article aims at the determination of relations between the real estate market and water supply and sewage management based on the example of the Lublin Functional Area (LFA). The paper is composed of two parts. The first part focuses on the characteristics of functional urban areas (FUA) both in the context of theoretical assumptions and practical aspects of their implementation under the Cohesion Policy 2014–2020 in Poland, as well as development problems of FUA resulting from the intensity of the process of suburbanization. The second part of the article presents the characteristics of LFA and the analysis of the relations between an increase in dwelling stock and the real estate market in the communes of LFA and their provision in water supply and sewage infrastructure. It also presents problems caused by uncontrolled expansion of built-up areas in the context of conducting sustainable municipal management in areas with high values for agricultural production in spatial, socio-economic, and environmental terms.